The role of MDM2 amplification and overexpression in therapeutic resistance of malignant tumors - Hou, Helei (Cancer Cell Int, 2019)
The MDM2 protein encoded by the mouse double minute 2 (MDM2) gene is the primary negative regulatory factor of the p53 protein. MDM2 can ligate the p53 protein via its E3 ubiquitin ligase, and the ubiquitinated p53 can be transferred to the cytoplasm and degraded by proteasomes. Therefore, MDM2 can maintain the stability of p53 signaling pathway. MDM2 amplification has been detected in many human malignancies, including lung cancer, colon cancer and other malignancies. MDM2 overexpression is associated with chemotherapeutic resistance in human malignancies. The mechanisms of chemotherapeutic resistance by MDM2 overexpression mainly include the p53–MDM2 loop-dependent and p53–MDM2 loop-independent pathways. But the role of MDM2 overexpression in tyrosine kinase inhibitors resistance remains to be further study. This paper reviews the possible mechanisms of therapeutic resistance of malignancies induced by MDM2 amplification and overexpression, including chemotherapy, radiotherapy, targeted agents and hyperprogressive disease of immunotherapy. Besides, MDM2-targeted therapy may be a potential new strategy for treating advanced malignancies.